Edukasi Higiene Peralatan Makan dan Menutup Makanan Bagi Siswa SDN 132/I dan Anak-Anak Suku Anak Dalam Hajran: Education on Hygiene of Eating Utensils and Covering Food for Students of SDN132/I and Children Suku Anak Dalam Hajran - Karen Rachma Audina; Fairuz Puteri Fadhillah; Shintia Nadila; Risya Amri; Renandita Fona Wirani Putri; Asywa Keisya Pratika; Nurfauzil Azima; Maitsa 'Aliyyah; Angel Amelia; Lara Setiani; Maria Indriyani Manulang; Arnati Wulansari (Jurnal Pengabdian Kepada Masyarakat: Kesehatan, 2026)
Abstrak: Masalah diare yang sering muncul di wilayah tersebut berkaitan dengan kebiasaan menyimpan makanan dalam kondisi terbuka dan penggunaan alat makan yang kurang higienis. Kegiatan pengabdian ini bertujuan meningkatkan pengetahuan mengenai higiene peralatan makan dan cara menutup makanan dengan benar pada siswa kelas 4 SDN 132/I serta kelompok Suku Anak Dalam (SAD) di Desa Hajran, Kecamatan Bathin XXIV, Kabupaten Batanghari. Kegiatan dilaksanakan pada November 2025 melalui edukasi menggunakan media PowerPoint, poster, demonstrasi praktik, ice breaking, serta evaluasi melalui pre-test dan post-test pada siswa sekolah, dan sesi dialog pada kelompok SAD. Hasil pre-test di SDN 132/I menunjukkan kategori Cukup 40%, Kurang 30%, Baik 20%, dan Sangat Baik 10%. Setelah edukasi, terjadi peningkatan dengan Baik naik menjadi 30% dan Sangat Baik menjadi 20%, serta penurunan kategori Cukup menjadi 30% dan Kurang menjadi 20%. Pada kelompok SAD, pre-test menunjukkan Cukup 50%, Baik 33%, dan Sangat Baik 17%. Setelah intervensi, terjadi peningkatan signifikan dengan hanya dua kategori yang muncul, yakni Sangat Baik meningkat menjadi 50% dan Baik menjadi 33%, tanpa kategori Cukup maupun Kurang, menandakan peningkatan pemahaman yang lebih merata.   Abstract: Frequent diarrhea in the area is related to the habit of storing food openly and using unhygienic eating utensils. This community service activity aimed to increase knowledge about eating utensils hygiene and how to properly cover food among fourth-grade students of SDN 132/I and the Suku Anak Dalam (SAD) group in Hajran Village, Bathin XXIV District, Batanghari Regency. The activity was conducted in November 2025 through educational sessions using PowerPoint presentations, posters, practical demonstrations, icebreakers, and evaluations through pre- and post-tests for students, and dialogue sessions for the SAD group. The pre-test results at SDN 132/I showed 40% of students receiving adequate food hygiene, 30% of students receiving inadequate food hygiene, 20% of students receiving good food hygiene, and 10% of students receiving excellent food hygiene. After the education, there was an increase, with 30% receiving good food hygiene and 20% receiving very good food hygiene. The Sufficient category decreased to 30% and 20% for the Sufficient category decreased to 30% and 20% for the Poor category. In the SAD group, the pre-test showed 50% receiving adequate food hygiene, 33% receiving good food hygiene, and 17% receiving very good food hygiene. After the intervention, there was a significant increase with only two categories appearing, namely Very Good increasing to 50% and Good to 33%, with no categories of Sufficient or Less, indicating a more even increase in understanding.